The Effect of Communicational Skills Training on Social Anxiety in Boys Adolescents with Intellectual Disability - sgf gfsdg; sgs dfsdf; afsaf fsdfd (Ravānshināsī-i Afrād-i Istis̠nāyī, 2016)
This study examined the effect of communicational skills training on social anxiety in boys adolescents with intellectual disability in Yazd. The current investigation was Experimental method and design of this study was pretest-posttest with control group type and the population included boys with intellectual disability 11-20 years intellectual disability special schools in Yazd in the academic year 2014-2015. The sample of this study included 40 students that randomly selected and divided into experiment and control groups (20 persons in each group). The instruments used in this study was La Greca Social Anxiety Scale for Adolescents (SAS-A). The communicational skills training program including 12 sessions of 50 minutes was carried to the experimental group. Descriptive statistics and inferential statistics such as independent t-test and variance analysis was used for data analysis.The Results of this study showed that there is a significant difference between experiment and control groups among social anxiety and all its dimension (p<0/01). The obtained results of data analysis demonstrated that communicational skills training decreased social anxiety (58%) and its components [fear of negative evaluation; social avoidance and distress in new situations; and social avoidance and distress-general (59/30%)] in adolescents of experimental group in compare with control group. Therefore, the research suggests to emphasis on communicational skills training for student with intellectual disability.